A Linked-HMM Model for Voicing and Speech Detection - Basu, Sumit (Institute of Electrical and Electronics Engineers, Inc., 2003)
We present a novel method for simultaneous voicing and speech detection based on a linked-HMM architecture, with robust features that are independent of the signal energy. Because this approach models the change in dynamics between speech and nonspeech regions, it is robust to low sampling rates, significant levels of additive noise, and large distances from the microphone. We demonstrate the performance of our method in a variety of testing conditions and also compare it to other methods reported in the literature.